1978
DOI: 10.1002/1097-0142(197806)41:6<2481::aid-cncr2820410658>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Familial intraocular malignant melanoma.A Case Report

Abstract: A family with histopathologically proven intraocular malignant melanoma involving two generations is reported. A member of third generation was likely involved by history. Intraocular malignant melanoma, its familial occurrence, its occurrence with multiple malignancies, and its relationship to multiple malignancies occurring in a family are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A PubMed search was directed with the key words “familial uveal melanoma,” “familial ocular melanoma,” and “familial eye melanoma”. Excluding reports by our own group, a total of 28 articles describing 115 independent families with multiple UM diagnoses were identified (https://docs.google.com/spreadsheets/d/1rb0qu-4d_rPjW7qs6G1-GyfEsepWtas40QM230_4Dfg/edit?usp=sharing: Lynch et al, ; Green et al, ; Oosterhuis et al, ; Canning and Hungerford, ; Jay and McCartney, ; Young et al, ; Wang et al, ; Singh et al, , , ; van Hees et al, ; Soufir et al, ; Krygier et al, ; Hearle et al, ; Kodjikian et al, ; Barker‐Griffith and Streeten, ; Jonsson et al, ; Smith et al, ; Njauw et al, ; Wadt et al, , ; Aoude et al, ; Cheung et al, ; Hoiom et al, ; Popova et al, ; Maerker et al, ; Gupta et al, ; Turunen et al, ). Out of those, 39 families had undergone BAP1 testing; seven of these were single case reports.…”
Section: Methodsmentioning
confidence: 99%
“…A PubMed search was directed with the key words “familial uveal melanoma,” “familial ocular melanoma,” and “familial eye melanoma”. Excluding reports by our own group, a total of 28 articles describing 115 independent families with multiple UM diagnoses were identified (https://docs.google.com/spreadsheets/d/1rb0qu-4d_rPjW7qs6G1-GyfEsepWtas40QM230_4Dfg/edit?usp=sharing: Lynch et al, ; Green et al, ; Oosterhuis et al, ; Canning and Hungerford, ; Jay and McCartney, ; Young et al, ; Wang et al, ; Singh et al, , , ; van Hees et al, ; Soufir et al, ; Krygier et al, ; Hearle et al, ; Kodjikian et al, ; Barker‐Griffith and Streeten, ; Jonsson et al, ; Smith et al, ; Njauw et al, ; Wadt et al, , ; Aoude et al, ; Cheung et al, ; Hoiom et al, ; Popova et al, ; Maerker et al, ; Gupta et al, ; Turunen et al, ). Out of those, 39 families had undergone BAP1 testing; seven of these were single case reports.…”
Section: Methodsmentioning
confidence: 99%
“…In the two other cases, the histology showed a mixed‐cell melanoma and a B spindle‐cell melanoma. Histopathological studies published in the literature showed that mixed‐cell melanoma was the predominant cell type (Bowen et al 1964; Green et al 1978; Walker et al 1979; Canning & Hungerford 1988; Singh et al 1996a), followed by spindle‐cell melanoma (Pfingst & Graves 1921; Simons et al 1983; Singh et al 1996a) (60% and 32%, respectively, in Singh et al 1996a). Within one set of kindred, histopathological findings were often uniform.…”
Section: Discussionmentioning
confidence: 99%
“…A second primary malignant neoplasm in the probands (Green et al 1978; Young et al 1994; Singh et al 1996a; Krygier et al 2001) or malignant neoplasm in the probands' relatives (Lynch et al 1968; Green et al 1978; Young et al 1994; Singh et al 1996a; Krygier et al 2001) seems to be rather common. Singh et al (1996a) estimated that the presence of a second primary malignant neoplasm was four times higher in probands of familial uveal melanoma than the expected prevalence of other cancers (all sites), based on data on age‐ and sex‐specific prevalence derived from the Connecticut Tumor Registry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations